Ts. Mohd. Najib, researcher cum entrepreneur formulates oily wastewater treatment product - UMP, PNC (2019)
The issues of uncontrolled oily wastewater discharge and water pollution that affect the environment inspire a lecturer from the Faculty of Chemical and Process Engineering Technology, Universiti Malaysia Pahang (UMP), Ts. Mohd Najib Razali to conduct research on the treatment of oily wastewater.